(untitled) (Annual of the Faculty of Philosophy in Skopje, 2013)
No serious research has yet been undertaken on the ceramic vessels produced in Macedonia during the Ottoman period. This paper attempts to present the most typical qualities of this rich ceramic output on the basis of a selection of materials recovered from the site of the citadel of Skopsko Kale, the site of the Isar Fortress in Stip, and from a private collection. The ceramic vessels produced before the arrival of the Ottomans differed only in certain aspects from the vessels produced thereafter—the main differences being in the ways in which ceramic vessels were used in preparing, preserving and serving food in Christian funereal rites, as well as in certain everyday needs and various technological or technical procedures. There is thus a certain degree of continuity in the appearance and the purpose of most of the ceramic types produced in Macedonia during the medieval Ottoman period, including the earthenware baking vessels, the amphora, flat- bottomed pans, earthenware tumblers, clay chalices, pitchers, incense-burners, plates for communion bread, and acoustic vessels (resonators). Stretching across three continents at the height of its power, the Ottoman Empire absorbed many influences from diverse spheres of life and culture, including a range of techniques and tastes in vessel production: from China and the Far East, from Pontus and the Balkans and, of course, from earlier Byzantine culture. Glazes were used in this period not only for luxurious tableware but also for ceramic vessels intended for everyday use. In each case, indeed, there were rules dictating which part of the vessel was to be glazed—the inner or outer side, the whole surface, or only the spout and the edges. Decoration took the form of painting in white or green colours with simple or colourful sgraffito techniques. Green glazes were most favoured by potters in the Ottoman period, with shades ranging from bright to almost black. Olive, yellowish and brown shades were also popular. The widespread consumption of tobacco from the beginning of the 17th century resulted in the prolific production of tobacco pipes. The production of pipes was mostly carried out by specialized craftsmen using highly refined clay. Only rarely were pipes produced by non-specialists, usually local potters whose pipes were typically of lower quality. Ottoman tastes and techniques in ceramics had a significant influence on traditional practices of Macedonian potters. This ethnological material has survived to the present day as a living part of Macedonian folk culture.